Methods in stream ecology - F.Richard Hauer and Gary A.Lamberti (Elsevier, 2017)
"In this revised and updated edition of the best-selling Methods in Stream Ecology, an international team of contributing authors describe the latest advances in the measurement, analysis, and assessment of stream ecosystems. This first volume of a two-volume series presents methods to assess the physical and biological structure of streams and includes full sections on Physical Processes, Stream Biota, and Community Interactions in 22 detailed chapters. Each chapter,contains basic methods suitable for teaching undergraduate or graduate students, along with advanced methods appropriate for research-level studies. Suitable as a textbook for courses in stream or river ecology, this book is also an important reference for professional aquatic ecologists, natural resource managers, and user groups seeking to evaluate the condition of streams of their watersheds"--